THE OBVIOUSNESS OF THE ARTICLE ON BODY SHAMING AGAINST CYBERBULLYING ON SOCIAL MEDIA BASED ON THE ITE LAW - Rohman, Muhammad Holilur; Rusdiana, Erma (JCH (Jurnal Cendekia Hukum), 2023)
Insulting the shape of the human Body, or what is familiarly known as body shaming, is an action by someone to criticize another individual's body shape, which originates from the imperfection of the body shape generally originates from; body shape is not ideal. Physique is not perfect, or there is a physical disability. The act of insulting the shape of the human Body or body shaming can be carried out verbally by carrying out direct insults aimed at insulting the individual, or an individual can criticize verbally and indirectly; in this case, the use of social media such as TikTok, Instagram, Facebook, Twitter. The research method used in this research is normative research. The results of the discussion obtained are that legally, the criminal act of insulting (body shaming) on social media can be subject to the provisions of the Law on ITE if the insult or body shaming is conveyed on social media and is expressed in the form of insults, ridicule, face, skin colour, and a person's body posture. So, this is included in the category of provisions of Article 27 paragraph (3) in conjunction with Article 45 paragraph (3) of Law No. 19 of 2016 concerning ITE. The legal protection provided to victims in criminal acts of insulting (body shaming) through social media is through LPSK, in the provisions of article 28 paragraph (1) of Law No. 31 of 2014 concerning the Protection of witnesses and victims.